The Diversity of Postharvest Fungi on Sidempuan Salak (Salacca Sumatrana Becc.) - Kiki Nurtjahtja (Talenta Publisher, 2022)
Salak fruit in Indonesia was produced by various cultivated varieties, one of which is sidempuan salak (Salacca sumatrana). Post-harvest destroying fungi is one of the most causes yield losses on sidempuan salak. The purpose of this study was to enumerate and the pathogenicity of postharvest destroying fungi on postharvest sidempuan salak. As many as 1000 g of fresh harvested of salak fruit was used as sample. Fungal population was enumerated by dilution method followed by pour plate method. The intensity of infection each of fungal species was determined. The results showed that there were five species of postharvest fungi that caused spoilage to sidempuan salak fruit i.e., Penicillium citrinum, mycelia sterilia, Aspergillus sp. A. niger and Penicillium. sp. Among of the fungi A. niger was the highest population (7.0×107 CFU/g) and the most predominant with intensity of infection was 100%.